Hubungan Supervisi Kepala Ruangan dengan Pelaksanaan Patient Safety di Ruangan Rawat Inap RS. Tk III Reksodiwiryo Padang Tahun 2025 - Hamda Sulfi Nadia; Asmawati .; Conny Oktizulvia (CV. ITTC INDONESIA, 2026)
According to the 2023 patient safety incident report from the KKP-RS, adverse events (KTD) in Indonesia increased from 46.2% to 63%. Patient safety is a significant issue in West Sumatra, with incident reporting occurring in only 3.8% of hospitals. The purpose of this study was to examine the relationship between ward head supervision and patient safety implementation in the Inpatient Ward of Reksodiwiryo Level III Hospital, Padang, in 2025. This was an analytical study with a cross-sectional design. The study was conducted from March to August 2025. Data collection took place from June 15 to 30, 2025. The population in this study was all nurses in the inpatient ward at Reksodiwiryo Hospital Level III, Padang, in 2025. A total of 104 nurses were selected, with a sample size of 51. The sampling technique used was simple random sampling. The study used a questionnaire and interviews. Data were analyzed univariately and bivariately using the Chi-Square statistical test with a 95% confidence level and a α value of 0.05. The results showed that more than half (60.8%) of respondents performed poorly on patient safety measures. Less than half (49%) of ward heads performed poorly on patient safety measures. There was a correlation between ward head supervision and patient safety implementation in the Inpatient Ward of Dr. Reksodiwiryo Hospital Class III, Padang, in 2025 (p-value = 0.000). The conclusion of the supervision of the head of the room is related to the Implementation of Patient Safety in the Inpatient Room of RS. Level III Reksodiwiryo Padang in 2025. It is hoped that the hospital will provide training on supervision to the head of the room. To improve the culture of patient safety in the inpatient room, the head of the room should be someone who has experience with a work period of > 5 years.